Saint Lawrence Seaway Additional Locks Study. Geotechnical Report. - Bobal,Thomas (1981)
This report presents geotechnical data used to assist in the selection of future additional lock and channel locations at four proposed alternative sites along a section of the St. Lawrence Seaway. The proposed alternatives include: 'Twin' locks at the existing Eisenhower and Snell locks, a single high-lift lock with the construction of a new channel, and an additional lock near Iroquois Dam at Point Rockway with construction of a new channel. All the proposed alternative sites are located within the territory of the United States along the St. Lawrence Seaway stretching from near Iroquois Dam downstream to the eastern tip of Cornwall Island near Cornwall, Ontario. Three of the sites, Eisenhower and Snell 'Twins' and the high-lift are located at the eastern end of the area, northeast of Massena, New York; and the fourth site, Iroquois-Point Rockway, at the western end near Waddington, New York. The report presents data from a review of literature and includes subsurface and geophysical exploration data, observations arrived at from on-site reconnaissance and discussions with individuals familiar with the area in question, examination of existing rock core samples previously taken at some of the proposed sites, summaries of field and laboratory testing and geologic profiles and sections based on data from previous subsurface exploration programs.